A numerical scheme for investigating the effect of bimodal structure on acoustic behavior of polylactide foams. (February 2015) - Ghaffari Mosanenzadeh, Shahrzad; Doutres, Olivier; Naguib, Hani E.; Park, Chul B.; Atalla, Noureddine
Abstract : Graphical abstract: This study presents the sound absorption properties of a novel bimodal foam structure made of polylactide (PLA) with an interconnected network of pores and micropores of very different characteristic sizes, fabricated utilizing the blend of PLA and polyethylene glycol (PEG) water soluble polymer. The goal is to investigate the link between microstructure and macroscopic properties of such materials to understand the acoustic behavior of porous membranes. The unique cubic cell structure of the fabricated foams is ideal for modeling purposes. Highlights: Polylactide (PLA) is used as the foam matrix to fabricate bio-based acoustic foams. Bimodal structure is studied as the practical solution for acoustic applications. Numerical method based on JCA models is applied to bimodal open cell PLA foams. Effect of bimodal structure on acoustic and non-acoustic properties is investigated. Presented bio-based foam can replace conventional petrochemical based acoustic foam. Abstract: In order to understand the acoustic behavior of porous membranes, there is a need to further investigate the link between microstructure and macroscopic properties of such materials. This study presents the sound absorption properties of a novel bimodal foam structure made of polylactide (PLA) with an interconnected network of pores and micropores of very different characteristic sizes, fabricated utilizing the blend of PLA and polyethylene glycol (PEG) water soluble polymer. Fabricated foams are bio-based and have the advantage of resolving the environmental concerns raised by petrochemical based sound absorbers. The purpose of this study is to develop bio-based open cell structures as a practical solution to today's needs for noise control resolutions. Acoustic performance of the bimodal PLA foams is studied by measuring the normal incident absorption coefficient and the effect of bimodal structure is investigated in terms of acoustic properties (i.e., sound absorption) and non-acoustic properties associated to the Johnson–Champoux–Allard model (i.e., porosity, airflow resistivity, tortuosity, …). Inverse method based on JCA model and impedance tube measurements for normal incident absorption coefficient was applied to estimate tortuosity and characteristic lengths. Results of inverse method are in good agreement with direct measurements of normal incident absorption coefficient. While tortuosity increases by increasing the polymer weight percent, it remains constant as the secondary porous structure extends in the porous medium. As the bimodal structure extends through the foam, both thermal and viscous characteristic lengths increase for different foam categories.